2001
DOI: 10.1016/s0042-6989(01)00075-x
|View full text |Cite
|
Sign up to set email alerts
|

Building surfaces from borders in Areas 17 and 18 of the cat

Abstract: Several brightness illusions indicate that borders can dramatically affect the perception of adjoining surfaces. In the Craik-O'Brien-Cornsweet illusion, in particular, two equiluminant surfaces can appear different in brightness due to the contrast border between them. Although the psychophysical nature of this phenomenon has been well characterized, the neural circuitry underlying this effect is unexplored. Here, we have asked whether there are cells in visual cortex which respond to edge-induced illusory br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 40 publications
6
37
2
Order By: Relevance
“…Neurophysiological studies in monkey suggest that a subpopulation of V1 and V2 neurons respond to luminance modulations well outside their classical receptive field (Kinoshita and Komatsu, 2001;Roe et al, 2005), in a manner qualitatively consistent with brightness perception. Similar results have been reported in cats (Rossi et al, 1996;Rossi and Paradiso, 1999;Hung et al, 2001). Friedman et al (2003), however, found no evidence for color filling-in signals in V1 and V2 of awake behaving monkeys.…”
Section: Comparison To Neurophysiological Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Neurophysiological studies in monkey suggest that a subpopulation of V1 and V2 neurons respond to luminance modulations well outside their classical receptive field (Kinoshita and Komatsu, 2001;Roe et al, 2005), in a manner qualitatively consistent with brightness perception. Similar results have been reported in cats (Rossi et al, 1996;Rossi and Paradiso, 1999;Hung et al, 2001). Friedman et al (2003), however, found no evidence for color filling-in signals in V1 and V2 of awake behaving monkeys.…”
Section: Comparison To Neurophysiological Resultssupporting
confidence: 85%
“…Recent modeling work suggests that the majority of V1 responses reported by Kinoshita and Komatsu (2001) can be understood on the basis of local and mean luminance processing and that only a small minority of responses are consistent with edge-driven surface activity, such as brightness filling-in (Vladusich et al, 2006). We speculate that the properties of these previously determined surface-responsive neurons (Rossi et al, 1996;MacEvoy et al, 1998;Rossi and Paradiso, 1999;Hung et al, 2001;Kinoshita and Komatsu, 2001;Roe et al, 2005) may in fact arise from the mechanisms underlying the extended edge responses we observed in our study, and so are presumably not directly related to our perception of brightness, color, or filling-in.…”
Section: Comparison To Neurophysiological Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The perceived brightness of a surface depends not only on surface luminance but also on the luminance distribution in the surrounding visual field (26, ʈ). It has already been demonstrated in cats and monkeys that single neurons in primary visual cortex exhibit a surround modulation that matches contextual effects in human brightness perception (6,9,27,28). By establishing the dynamics of surface-related responses in early visual cortex, our findings therefore provide the fundamental information necessary for the interpretation of future neuroimaging studies of contextual effects in human subjects.…”
Section: Discussionsupporting
confidence: 66%
“…How the brain encodes such local and global brightness cues is unknown. Only a few studies have examined neuronal response to uniform surfaces (4)(5)(6)(7)(8)(9). These studies have shown that although cells modulated by luminance change are found as early as the retina and lateral geniculate nucleus (LGN), those modulated by perceived brightness change, which occur independent of actual luminance change over the receptive field (RF), can be found as early as the primary visual cortex (V1).…”
mentioning
confidence: 99%